Abyssal and forearc features of mantle peridotites in the Guleman ophiolite in SE Turkey - Rizeli, Mustafa Eren; Bingol, Ahmet Feyzi; Wang, Kuo-Lung; Lee, Hao-Yang (Elsevier, 2023)
The mantle section of the Guleman ophiolite consists mainly of depleted harzburgite and dunite with some less depleted harzburgite, all of which contain economically significant chromitite. The depleted harzburgite and dunite are characterized by low average bulk Al2O3 (<0.85 wt%) and CaO (0.14-0.94 wt%) contents, high-Mg olivine (Fo = 90.8-93.8) and orthopyroxene (Mg# = 91.3-92.1) together with moderately high-Cr spinel (Cr# = 54.1-67.6). The less depleted harzburgite (sample EG30) contains higher bulk Al2O3 (1.84 wt%) and CaO (2.15 wt%) contents, slightly lower-Mg olivine (Fo = 90.4) and orthopyroxene (Mg# = 90.4) together with lower-Cr spinel (Cr# = 17.9) and clinopyroxene with high Al2O3 (2.79 wt%) and similar TiO2 (0.05 wt%) contents. The Os-187/Os-188 isotopic ratios of the Guleman peridotites are 0.12589, 0.12736 and 0.13352, coupled with Re-187/Os-188 ratios of 0.32822, 0.90743, and 1.48804, respectively, for the dunite and depleted harzburgite These data suggest that the Guleman peridotites were modified by melt metasomatism and/or Re addition. Petrographical and geochemical results reveal that mantle peridotites experienced multi-stage melting and refertilization. In the first stage, abyssal peridotites were formed by similar to 15% partial melting of an upwelling mantle at a mid-ocean ridge under anhydrous conditions, which was followed by the second stage of partial melting in a supra-subduction zone environment under hydrous conditions. In this later stage, forearc peridotites were formed with a total of 25-43% partial melting for the two episodes and then refertilized. However, some of the peridotites were unaffected (or less affected) by these later events. As a result, abyssal and forearc peridotites are both observed in the Guleman ophiolite.
Keywords: Guleman ophiolite; Abyssal peridotites; Forearc peridotites; Partial melting; Mineral chemistry; Turkey